2018
DOI: 10.1111/wrr.12667
|View full text |Cite
|
Sign up to set email alerts
|

Deferoxamine can prevent pressure ulcers and accelerate healing in aged mice

Abstract: Chronic wounds are a significant medical and economic problem worldwide. Individuals over the age of 65 are particularly vulnerable to pressure ulcers and impaired wound healing. With this demographic growing rapidly, there is a need for effective treatments. We have previously demonstrated that defective hypoxia signaling through destabilization of the master hypoxia-inducible factor 1α (HIF-1α) underlies impairments in both aging and diabetic wound healing. To stabilize HIF-1α, we developed a transdermal del… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 16 publications
0
20
0
Order By: Relevance
“…[ 117 ] suggest that iron deposition caused delayed healing in diabetic foot ulcers, promoting an unrestrained M1-like macrophage phenotype, increased oxidative stress and senescence. Similarly, others have shown that the iron chelator, deferoxamine, improves wound healing in pressure ulcers of diabetic [ 147 ] and aged [ 148 ] mice. Thus, the cellular effects of iron are probably context-dependent and wound-type-specific, exacerbating tissue damage in an already pro-inflammatory environment, while promoting alternatively activated macrophage- and fibroblast-mediated wound resolution in late-stage repair.…”
Section: When Healing Fails—factors Influencing Chronic Wound Healingmentioning
confidence: 96%
“…[ 117 ] suggest that iron deposition caused delayed healing in diabetic foot ulcers, promoting an unrestrained M1-like macrophage phenotype, increased oxidative stress and senescence. Similarly, others have shown that the iron chelator, deferoxamine, improves wound healing in pressure ulcers of diabetic [ 147 ] and aged [ 148 ] mice. Thus, the cellular effects of iron are probably context-dependent and wound-type-specific, exacerbating tissue damage in an already pro-inflammatory environment, while promoting alternatively activated macrophage- and fibroblast-mediated wound resolution in late-stage repair.…”
Section: When Healing Fails—factors Influencing Chronic Wound Healingmentioning
confidence: 96%
“…DFO has promise as a safe, effective treatment with the potential to fill this void, but uncertainty remains regarding the best delivery route. Recently, topical administration of DFO has been studied in wound‐healing experiments 22‐25 22 .…”
Section: Introductionmentioning
confidence: 99%
“…[ 9–15 ] As reported in previous studies, tissue injuries lead to site‐dependent environmental changes and abnormal cellular activity. Multiple factors, including enzymes, [ 16–36 ] reduction and oxidation (redox) reactions, [ 37–44 ] hypoxia, [ 32,45–49 ] pH, [ 47,50–54 ] temperature, [ 55–57 ] and the other characteristics, [ 42,58–60 ] become dysregulated at the onset of injury or during the progression of the healing ( Figure A). These hallmarks can be monitored to serve as a reference to evaluate the extent of injury, stage of wound healing, and necessity for treatment.…”
Section: Introductionmentioning
confidence: 99%